2021
DOI: 10.21203/rs.3.rs-664507/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Myeloid cell interferon responses correlate with clearance of SARS-CoV-2

Abstract: The emergence of mutant SARS-CoV-2 strains associated with an increased risk of COVID-19-related death necessitates better understanding of the early viral dynamics, host responses and immunopathology. While studies have reported immune profiling using single cell RNA sequencing in terminal human COVID-19 patients, performing longitudinal immune cell dynamics in humans is challenging. Macaques are a suitable model of SARS-CoV-2 infection. We performed longitudinal single-cell RNA sequencing of bronchoalveolar … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 78 publications
(102 reference statements)
0
3
0
Order By: Relevance
“…In addition to using samples from COVID-19 patients for research, developing animal models for COVID-19 and subjecting them to scRNA-seq could facilitate preclinical analysis of vaccines and therapeutic agents. Although there are many studies using infected animals for COVID-19 research, 87,88 only a few studies performed scRNA-seq on COVID-19-infected animals like monkeys, 89 hamsters, 90 macaques, 91 ferrets, 92 and K18-hACE2 transgenic mice. 93 Several studies demonstrated the antiviral immune responses of animal models after receiving newly developed vaccines with scRNA-seq, [94][95][96][97] revealing induced gene modules of different immune cell populations.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…In addition to using samples from COVID-19 patients for research, developing animal models for COVID-19 and subjecting them to scRNA-seq could facilitate preclinical analysis of vaccines and therapeutic agents. Although there are many studies using infected animals for COVID-19 research, 87,88 only a few studies performed scRNA-seq on COVID-19-infected animals like monkeys, 89 hamsters, 90 macaques, 91 ferrets, 92 and K18-hACE2 transgenic mice. 93 Several studies demonstrated the antiviral immune responses of animal models after receiving newly developed vaccines with scRNA-seq, [94][95][96][97] revealing induced gene modules of different immune cell populations.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…This study gives additional mechanistic insights into how SARS-CoV-2 can hamper innate immune responses ( 39 ). Extensive work performed in the NHP model of SARS-CoV-2 infection indicates that these animals mount robust, early IFN responses, and simultaneously clear the infection ( 18 , 19 , 40 ). On the other hand, many humans with late to end-stage COVID-19 are characterized by a “cytokine storm” with IFN as the key cytokine.…”
Section: Immune Responsesmentioning
confidence: 99%
“…In addition to interfering with the IFN system, SARS-CoV-2 has also been shown to infect antigen-presenting cells (APCs) including dendritic cells, macrophages and monocytes, disrupting their primitive function of activating adaptive immunity ( 24 , 25 , 40 , 42 ). While these cells did not support viral production, their attenuated functions averted strong antibody but weak CD8 T cell responses ( 24 , 25 ).…”
Section: Immune Responsesmentioning
confidence: 99%